Surgically induced weight loss results in a rapid and consistent improvement of female pelvic floor symptoms. (4th May 2018) - Leshem, Avner; Groutz, Asnat; Amir, Hadar; Gordon, David; Shimonov, Mordechai
Abstract: Objective: The aim of this study was to evaluate the effect over time of bariatric surgery on female pelvic floor symptoms. Methods: In total, 160 consecutive adult women were requested to complete four anonymous questionnaires [International Consultation on Incontinence Questionnaire (ICIQ), Bristol Female Lower Urinary Tract Symptoms (BFLUTS), Pelvic Floor Distress Inventory (PFDI-20) and Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12)] before bariatric surgery and at 3–6 months and 12–24 months postoperatively. Strict criteria were used to define clinically significant urinary incontinence (UI), pelvic organ prolapse (POP) and colorectal–anal (CRA) symptoms. Statistical analyses were performed using paired, two-sided, Student's t test for continuous data, and Fisher's exact test for categorical data. Results: Altogether, 101 women (67%, mean age 41.6 ± 11.8 years, mean preoperative body mass index 41.6 ± 4.6 kg/m²) completed all questionnaires. In women who had preoperative UI (42.6%), mean ICIQ score decreased from 9.5 ± 4.0 at baseline to 3.0 ± 3.6 ( p < .001) and 2.9 ± 3.9 ( p < .001) at 3–6 and 12–24 months postoperatively, respectively. In women who had preoperative POP symptoms (17.8%), mean PFDI-20/POP score decreased from 23.8 ± 10.9 at baseline to 12.7 ± 12.9 ( p = .010) and 13.7 ± 17.1 ( p = .025) at 3–6 and 12–24 months postoperatively. In women who had preoperative CRA symptoms (35.6%), mean PFDI-20/CRA score decreased from 26.0 ± 14.9 at baseline to 15.4 ± 15.1 ( p = .001) and 18.8 ± 15.4 ( p = .045) at 3–6 and 12–24 months postoperatively. De novo postoperative POP and CRA symptoms were reported by up to 16% of patients. Conclusions: Surgically induced weight loss is associated with significant improvements in UI, POP and CRA symptoms. The maximal clinical effect was achieved within 3–6 months, and remained constant throughout the second postoperative year. Nevertheless, de novo POP and CRA symptoms are expected in up to 16% of patients.